-8(-6x-9)=9(-4x-6)
in Algebra 1 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

-8(-6x-9)=9(-4x-6),

48x+72=-36x-54,

48x+36x=-54-72,

84x=-126,

Divide both sides by 42:

2x=-3, x=-3/2.

CHECK Put x=-3/2 into the original equation:

-8(9-9)=9(6-6), so 0=0 OK.

Another way to solve: rewrite the original equation:

-24(-2x-3)=18(-2x-3) by factorising the contents of the parentheses,

42(-2x-3)=0, so, since 42 is not zero, -2x-3=0, 2x=-3, x=-3/2.

by Top Rated User (717k points)

Related questions

1 answer
asked Feb 18, 2013 in Algebra 1 Answers by anonymous | 186 views
1 answer
asked Feb 4, 2013 in Algebra 2 Answers by anonymous | 185 views
1 answer
0 answers
1 answer
asked Nov 5, 2011 in Pre-Algebra Answers by anonymous | 715 views
1 answer
1 answer
asked May 21, 2013 in Algebra 1 Answers by anonymous | 95 views
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
84,493 questions
89,412 answers
1,998 comments
8,089 users